Wind Energy in Planning Visions and Practices in Contemporary China - He, Yuan (International Planning History Society Proceedings, 2024)
China is the leading player in the wind energy market, with nearly half of the current global installed wind energy capacity. Literature on wind energy development is dominated by the energy policy and engineering sciences domains and focuses on the economic and decarbonization potential of wind turbines. This paper aims to bring the actual resource (the wind) and the land on which the turbines are placed to the forefront of discussion and explore how these three components relate to each other. While wind as a natural resource is atmospheric and aterritorial, the technology that facilitates conversion into electricity is rooted in the ground. Wind energy in China was able to grow rapidly not only by way of strong state support, but also because regulations on natural reserve preservation were not strictly enforced, and wind farms were aestheticized as fitting into ecological landscapes. The paper concludes by looking forward to shifts in configurations of the resource, land, and technology prompting new path in wind energy development: turbines situated on nature reserves are mandated to be decommissioned under the concept of ecological civilisation, and various cultural meanings of wind continue to be used to rationalize the siting of wind turbines.